Kinerja Keuangan Daerah Kabupaten Sukoharjo Ditinjau dari Perspektif Otonomi Daerah - Arnita Febriana Puryatama; Kristina Setyowati (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
Regional finance has a pivotal role in regional autonomy because regional finance reflects the ability of regions in running the local government. One of the tools to analyze local government financial performance is ratio analysis. The purpose of this study was to determine how the regional financial performance of Sukoharjo Regency in terms of regional autonomy perspective. This research uses descriptive quantitative method. The data used in this research is secondary in the form of financial report data Sukoharjo regency in 2015-2019 were obtained using the time series technique. The analysis results show that the financial performance of Sukoharjo regency is still not optimal. This is indicated by lack of ability to extract local revenue known from the low of DDF ratio, DOF ratio, Fiscal capacity and fiscal effort. Other than that, low independence ratio indicates that the regional dependence on central financial is still high.